Functionalized Nanocomposite Gel Polymer Electrolyte with Strong Alkaline‐Tolerance and High Zinc Anode Stability for Ultralong‐Life Flexible Zinc–Air Batteries. Issue 7 (16th December 2022) - Fan, Xiayue; Wang, Haozhi; Liu, Xiaorui; Liu, Jie; Zhao, Naiqin; Zhong, Cheng; Hu, Wenbin; Lu, Jun
Abstract: Increasing pursuit of next‐generation wearable electronics has put forward the demand of reliable energy devices with high flexibility, durability, and enhanced electrochemical performances. Flexible aqueous zinc–air batteries (FAZABs) have attracted great interests owing to the high energy density, safety, and environmental benignity, for which quasi‐solid‐state gel polymer electrolytes (QSGPEs) are state‐of‐the‐art electrolytes with high ionic conductivity, flexibility, and resistance to leakage problems of traditional liquid electrolytes. Compared to commonly used PVA–KOH electrolyte with poor electrolyte retention capability and cycling stability, a new type of sulfonate functionalized nanocomposite QSGPE is applied in FAZABs with high ionic conductivity, strong alkaline tolerance, and high zinc anode stability. Notably, the existence of (1) strong anionic sulfonate groups of QSGPEs, contributing to the exposure of preferred Zn (002) plane that is more resistant to zinc dendrite formation, and (2) nano‐attapulgite electrolyte additives, beneficial for the enhancement of ionic conductivity, electrolyte uptake, and retention capability, endows a ultralong cycling life of 450 h for the fabricated FAZAB. Furthermore, flexible energy belts and knittable energy wires fabricated with a series/parallel unit of several FAZABs can be used to power various wearable electronics. Abstract : Flexible zinc–air batteries have attracted extensive interests, for which the quasi‐solid‐state gel polymer electrolytes (QSGPEs) are state‐of‐the‐art electrolytes. This study reports a sulfonate functionalized nanocomposite QSGPE with high ionic conductivity, strong alkaline tolerance, and high zinc anode stability, endowing an ultralong cycling life of 450 h and high power output for the fabricated zinc–air battery.